The Efectiveness of Arbitration Mechanisms in The Resolution Of Construction Disputes In Indonesia: A Critical Analysis of Law No. 30 of 1999 on Arbitration And Alternative Dispute Resolution - Pakpahan, Alfredo; Saragih, Hidbar Roberta; Wisatrioda, Bayu; Laia, Kharisman; Hardjomuljadi, Sarwono; Sami’an, Sami’an (Journal of Law, Politic and Humanities, 2025)
Disputes in construction projects often arise from divergent interpretations of contracts, delays in execution, and the complex dynamics of scope changes. Within this context, arbitration has long been regarded as an alternative dispute resolution mechanism that promises efficiency, fairness, and confidentiality outside the court system. However, more than two decades after the enactment of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, its effectiveness in the construction sector remains subject to debate and scrutiny. This study critically examines the effectiveness of arbitration in resolving construction disputes under the legal framework established by Law No. 30 of 1999. Using a normative juridical approach, it reviews statutory regulations, legal doctrines, and field practices, complemented by interviews with legal practitioners and construction arbitrators. The findings reveal that while arbitration offers advantages in terms of confidentiality, procedural flexibility, and finality of decisions, its practical effectiveness is often constrained by high procedural costs, limited contractual understanding among parties, and challenges in enforcing arbitral awards through the courts. Furthermore, the substance of Law No. 30 of 1999 appears insufficiently adaptive to the technical and multidimensional nature of modern construction disputes. This research therefore recommends revising and modernizing the law particularly by strengthening the enforceability of arbitral awards, standardizing arbitration institutions, and enhancing the competence of human resources in construction law. Ultimately, arbitration should evolve as a mechanism not only for efficient dispute resolution but also for upholding justice, legal certainty, and professional integrity in Indonesia’s construction sector.